Tangible programming in the classroom with Tern. - Horn, Michael S.; Jacob, Robert J. K. (Tufts University. Tisch Library., 2017)
This interactivity demonstrates Tern, a tangible programming language for middle school and late elementary school students. Tern consists of a collection of wooden blocks shaped like jigsaw puzzle pieces. Children connect these blocks to form physical computer programs, which may include action commands, loops, branches, and subroutines. With Tern we attempt to provide the ability for teachers to conduct engaging programming activities in their classrooms, even if there are only one or two computers available. In designing Tern, we focused on creating an inexpensive, durable, and practical system for classroom use.